224k views
2 votes
Evaluate the function g(x) = 2x2 + 3x – 5 for the input values -2, 0, and 3.

g(-2) = -2(-2)2 + 3(-2)-5
g(-2) = -2(4) – 6-5
g(-2) =
g(0) =
-
9(3) =

2 Answers

2 votes

Answer:

-19

-5

-14

Explanation:

User Damienfrancois
by
5.2k points
4 votes

Evaluate the function

g(x) = 2x2 + 3x – 5 for the input values -2, 0, and 3.

This is tedious math work but necessary to sharpen your skills.

Let x = -2

g(-2) = 2(-2)^2 + 3(-2) – 5

g(-2) = 2(4) - 6 - 5

g(-2) = 8 - 11

g(-2) = -3

Now let x = 0 and repeat the process.

g(0) = 2(0)^2 + 3(0) - 5

g(0) = 0 + 0 - 5

g(0) = -5

Lastly, let x = 3.

g(3) = 2(3)^2 + 3(3) - 5

g(3) = 2(9) + 9 - 5

g(3) = 18 + 9 - 5

g(3) = 27 - 5

g(3) = 22

Did you follow through each step?

User Mklbtz
by
5.2k points